Effect of BRAFmutational status on expression profiles in conventional papillary thyroid carcinomas. (December 2015) - Schulten, Hans-Juergen; Alotibi, Reem; Al-Ahmadi, Alaa; Ata, Manar; Karim, Sajjad; Huwait, Etimad; Gari, Mamdooh; Al-Ghamdi, Khalid; Al-Mashat, Faisal; Al-Hamour, Osman; Al-Qahtani, Mohammad; Al-Maghrabi, Jaudah
Abstract Background Whereas 40 % to 70 % of papillary thyroid carcinomas (PTCs) are characterized by aBRAF mutation (BRAF mut ), unified biomarkers for the genetically heterogeneous group ofBRAF wild type (BRAF wt ) PTCs are not established yet. Using state-of-the-art technology we compared RNA expression profiles between conventionalBRAF wt andBRAF mut PTCs. Methods Microarrays covering 36, 079 reference sequences were used to generate whole transcript expression profiles in 11BRAF wt PTCs including five micro PTCs, 14BRAF mut PTCs, and 7 normal thyroid specimens. Ap -value with a false discovery rate (FDR) < 0.05 and a fold change > 2 were used as a threshold of significance for differential expression. Network and pathway utilities were employed to interpret significance of expression data.BRAF mutational status was established by direct sequencing the hotspot region of exon 15. Results We identified 237 annotated genes that were significantly differentially expressed betweenBRAF wt andBRAF mut PTCs. Of these, 110 genes were down- and 127 were upregulated inBRAF wt compared toBRAF mut PTCs. A number of molecules involved in thyroid hormone metabolism includingthyroid peroxidase (TPO ) were differentially expressed between both groups. Among cancer-associated molecules wereERBB3 that was downregulated andERBB4 that was upregulated inBRAF wt PTCs. Two microRNAs were significantly differentially expressed of which miR492 bears predicted functions relevant to thyroid-specific molecules. The protein kinase A (PKA) and the G protein-coupled receptor pathways were identified as significantly related signaling cascades to the gene set of 237 genes. Furthermore, a network of interacting molecules was predicted on basis of the differentially expressed gene set. Conclusions The expression study focusing on affected genes that are differentially expressed betweenBRAF wt andBRAF mut conventional PTCs identified a number of molecules which are connected in a network and affect important canonical pathways. The identified gene set adds to our understanding of the tumor biology ofBRAF wt andBRAF mut PTCs and contains genes/biomarkers of interest.